Sifat-Sifat Fisikokimia Pati Ubi Kayu Terfermentasi Khamir Indigenus Tapai - Heru Widyatmoko; Achmad Subagio; Nurhayati Nurhayati (Agritech, 2018)
Tapai is a cassava food product fermented by yeast starter (“Ragi”). Among the amylolitic yeasts that had been isolated from the tapai were Candida guilliermondii, C. tropicalis, Trichosporon mucoides, and Saccharomycopsis fibuligera. The aim of this research was to characterize the physicochemical properties of fermented cassava starch by amylolytic yeasts of indigenus tapai i.e. C. guilliermondii, C. tropicalis, T. mucoides, and S. fibuligera. The process of fermentation of cassava starch was done by inoculating each pure isolate by 5% v / v (105 CFU / ml) into cassava starch suspension 50% b/v (100g starch into 200ml sterile distilled water). The incubation was carried out at 28 °C for 24 h, 48 h, and 72 h. The fermented cassava starch was dried at 50 °C for 24 h. Characterization of physicochemical properties of cassava starch included chemical properties (amylose content), paste properties (RVA), thermal properties (DSC), physical properties (SEM granule macrostructure) and functional groups (FT-IR) of unfermented (native) or fermented cassava starch. The results showed that during the fermentation process, the yeast was able to grow up to 7 log10 CFU/ml and the acidity decreased to pH 3,9. The amylose content of fermented cassava starch decreased to 11,22% from native starch amylose content (15,85%). The paste properties of fermented cassava starch increased at the value of trough viscosity, breakdown, final viscosity, and swelling power. The thermal properties of fermented cassava starch increased to 64,7-67 °C for the initial temperature value of gelatinization (To), 69,1-71,2 °C for gelatinization peak temperature (Tp), 73,9-75 °C for the final temperature of gelatinization (Tc), but decreased gelatinization enthalpy in the range of ΔH 4,84-6,38 J/g. The macrostructure of the longest fermented starch granules (72 hours)occurred liberation into irregular granular shapes. The profile of fermented cassava starch functional groups had a similarity with native cassava starch that had the highest absorption spectra at 3291,2 cm-1 peak (vibration of the O-H bonding group) and 2920 cm-1 peak (C-H group vibration).